Navigating Choices: Exploring Impact Of Product Descriptions On Regulatory Focus Goals In The Selection Of Hedonic And Utilitarian Products - Sharma, Srishti (My University, 2024)
This study delves into examining the modulatory nature of regulatory focus goals (promotion versus prevention) as a function of product descriptions (abstract versus concrete) on consumer behavior in terms of their trustworthiness and purchase intentions on the products. .The study aimed to discern whether varying descriptions prompt consumers to emphasize goal achievement or problem avoidance when navigating purchasing choices. Participants groups with promotion or prevention goals induced in them were exposed to diverse advertisements and probed about their sentiments (in terms of trustworthiness and purchase intention) regarding the products. The results demonstrate a notable alteration in consumer trust and purchase intention based on the description type employed for product descriptions. However, the type of group assigned to participants does not have a significant impact on purchase intention. Data was gathered via a qualtrics survey tool and subjected to analysis using statistical software (SPSS)
Keywords: Regulatory Focus Goals; Abstract –Concrete product description; Hedonic products; Utilitarian products; Consumer behavior